2003
DOI: 10.1258/135763303321327939
|View full text |Cite
|
Sign up to set email alerts
|

Tele-education in child mental health for rural allied health workers

Abstract: We developed a tele-education programme in child mental health for rural allied health workers. The programme was delivered in two parts, each consisting of six sessions. Videoconferencing at 384 kbit/s was used. Satisfactory retention rates were maintained throughout. Participants consistently reported increases in knowledge and skills as a result of attending the programme. The project resulted in a high rate of reported changes to practice. An unanticipated outcome was the value placed on the opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 3 publications
0
40
0
Order By: Relevance
“…Among the most frequently reported obstacles are time, cost and travel. 3,4 Clearly, alternative methods of providing clinical supervision are required.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most frequently reported obstacles are time, cost and travel. 3,4 Clearly, alternative methods of providing clinical supervision are required.…”
Section: Introductionmentioning
confidence: 99%
“…These can be streamed via the internet or transmitted via a number of ways including point-to-point circuits and the public Internet (if transmitting protected health information or other sensitive information via the public internet, AES encryption or a virtual private network (VPN) may be used to secure the transmission). 27 Distance education modalities can be used for clinical care of MHCU, e.g. teaching regarding medications, therapies, or compliance with treatment plans.…”
Section: • Distance Learningmentioning
confidence: 99%
“…Practitioners in rural areas lack easy access to continuing education (Fahey et al 2003). Conferences and other opportunities for professional development are often located in urban centres, requiring rural practitioners to travel great distances at significant expense and time away from their communities.…”
Section: Education and Trainingmentioning
confidence: 99%
“…It can also decrease their sense of professional isolation, improving the recruitment and retention of these practitioners in rural communities (Fahey et al 2003;Smith et al 2009;White et al 2007) Videoconferencing is one method of delivering educational services to practitioners in their communities. Most commonly, it has been used for delivering seminars, grand rounds and other similar presentations (Fahey et al 2003;Rees et al 2009), although there are reports of its use for clinical supervision of trainees and practitioners (Hilty et al 2004;Xavier et al 2007). Studies have demonstrated that education delivered by videoconference was perceived as relatively equivalent to face-to-face teaching (Whitten et al 1998).…”
Section: Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation